How technology shapes advice: professional–parent interaction in a digital pediatric treatment - Dalmaijer, Evi; Pas, Berber; Spooren, Wilbert; Stommel, Wyke (Frontiers in Communication, 2023)
Technology-enabled treatments (TET) have emerged in pediatric care as an effective solution for early and intensive intervention. There is a lack of research in the field of digitalized health care on the interaction between professionals and parents on which these treatments are based, and at the same time too little is known about the impact of remoteness and technology on interaction in the field of health communication. We use a conversation analytical approach to examine the interaction between occupational therapists and parents in one such treatment on a micro level, with a focus on advicegiving and the role of professional and parental authorities in this. Our analyses show that professionals in TET work together with the parents of children in treatment to achieve children's rehabilitation goals. In advice-giving in TET, the professionals interactionally downgrade their epistemic and deontic authority, orienting towards the imposition on parents inherent to advice and orienting towards parental authority. By describing three different patterns of the interactional unfolding of advice-giving, we provide insights into how professionals carefully initiate and return to advice and show how this activity is shaped by the technology used for the interaction. Our study offers a better understanding of how paramedical professionals practice their profession given remoteness and technology and what TET entails interactionally in terms of advice-giving.